Big social data and urban computing : first workshop, BiDU 2018, Rio de Janeiro, Brazil, August 31, 2018, Revised selected papers /: first workshop, BiDU 2018, Rio de Janeiro, Brazil, August 31, 2018, Revised selected papers. (2019) - Unknown
No abstract available